Mask use for athletes: A systematic review of safety and performance outcomes - Lott, A.; Roberts, T.; Carter, C. W. (Sports Health: A Multidisciplinary Approach, 2022)
Context: With the current Centers for Disease Control and Prevention recommendations for mask use to minimize transmission of coronavirus 2019 (COVID-19) coupled with concern for future pandemics that would require mask wearing, providing data-driven guidance with respect to athletic performance is essential.